Kedudukan Fraksi di Dewan Perwakilan Rakyat Republik Indonesia Pasca Reformasi - Fathan Ali Mubiina (Jurnal Konstitusi, 2020)
The Faction of Political Party in the Indonesian House of Representatives or Parliament is as a strategic forum in the political system in Indonesia in order to connect between the process of forming government policy both in the executive and legislative branches with its citizens as a form of structured channeling of aspirations. Because in political parties there is a form of institutionalization of the expression of ideas, thoughts, views, and free beliefs in a democratic society. Then the political parties also according to the laws and regulations in force in the history of the development of political parties after the reform is to function as political education, absorb, channel and fight for the interests of the community, and prepare community members to fill political positions in accordance with the existing democratic mechanism in Indonesia through representative democracy. The pattern of relations between political parties and the DPR RI is quite simple, namely political parties have the right to participate in the election process for legislative members in the DPR RI. This legal research is prescriptive in nature, which is carried out to solve the legal issues at hand.